Augmented virtuality technology in education: taxonomy of augmented virtuality types - Alexandr V. Grinshkun; Anastasia S. Zakova (RUDN Journal of Informatization in Education)
Problem statement. The authors discuss the interim results, which analyzed the least of all the studied immersive technologies - augmented virtuality technology and its educational potential. Various approaches to the augmented virtuality implementation by its addition with real objects are identified. Methodology. The most effective application spheres of augmented virtuality: transfer, copy, modified transfer, modified copy, are analysed. The augmented virtuality usage in education gives an opportunity to place a student into a virtual environment and increase the realism of the educational simulation significantly (in comparison with virtual reality technology) by maintaining the interaction with the real world. The transfer is the realization of a real object in virtual space in the line of sight. This technology allows to convey the object's appearance in the most efficient way, however, it reduces the immersion effect. The most productive usage can occur during work with people and with the presence of real objects. The copy is a virtual copy display without functional changes, presented as a 3D model instead of a real object. It allows to achieve maximum immersion and to implement relatively accurate interaction. The modified transfer is the real object implementation to the line of sight with functional and visual changes in the virtual space. This technology is most effective in conducting virtual excursions with a real guide and maximum immersion with the partial presence of real objects. It can be used while demonstrating physical phenomena with real objects. The modified copy is a display of a virtual copy with functional or visual changes in relation to the original object. It is advisable to use it in the absence of real objects or during developing practical skills. Results. Each adding virtuality method has its own advantages, disadvantages, implementation technologies and application areas. The choice depends on the educational task and learning conditions. Conclusion. The augmented virtuality usage in education gives an opportunity to place a student into a virtual environment and increase the realism of the educational simulation significantly (in comparison with virtual reality technology) by maintaining the interaction with the real world. The choice of one of the four main ways of reality adding should be determined by the goals, content and methods of teaching. Methods that are used in education may be combined in various combinations. This allows to apply augmented virtuality to various educational purposes.